(Dis)Connections and Silence: Experiences of Family and Part-time Work in Japan. Issue 2 (3rd May 2016) - Cook, Emma E.
ABSTRACT: Doing work that is characterized by instability and low incomes, Japanese male part-time workers often remain in the natal home well into adulthood even in cases where there is considerable discord and where familial bonds are strained or complicated. Through detailed case studies this article examines how, for some male part-time workers, a desire to disconnect from familial kin in the search for individual autonomy leads to the creation of alternative forms of relatedness. Meanwhile, for others, pressure to work in particular ways combined with the negotiations of complex family relationships – especially with (male) heads of households – contributes to alienation from family and society. Although work status is not the only cause of family strain, gendered work expectations and labour pressures considerably contribute to discord and can lead to significant experiences of social exclusion and disconnection from the family and wider society.